Pengaruh Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kinerja Karyawan Pada BRI Kantor Cabang Gorontalo - Buhungo, Suhardin; Niswatin; Santoso, Ivan Rahmat (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to determine the effect of accounting information systems and internal control on the performance of BRI Gorontalo Branch Office employees. The type of method used in this research is a quantitative method with data collection techniques using questionnaire surveys and observation. The number of respondents in this research was 40 respondents consisting of Branch Managers, Managers, Supper Visors, Tellers, CS, Marketing and Support at Bank BRI. The tool used in this research uses multiple linear regression analysis. The research results show that 1. Accounting information systems have a positive and significant effect on employee performance. 2. Internal control has a positive and significant effect on employee performance. 3. Simultaneously the accounting information system and internal control have a positive and significant effect on employee performance with a determinant value of 62.3% while the remaining 37.7% is explained by other variables not examined in this research.